2020
DOI: 10.15562/phpma.v8i1.232
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between anxiety and sleep quality in patients attending Kecamatan Penjaringan Public Health Center, North Jakarta

Abstract: Background and purpose: Anxiety is generally found in primary health care patients with physical problems and are often not treated. This condition can affect the patient's sleep quality. The aim of this study was to determine the relationship between anxiety and sleep quality in patients attending Kecamatan Penjaringan Public Health Center (PHC), North Jakarta.Methods: This is a cross-sectional study of 434 patients attending the health care service of Kecamatan Penjaringan PHC, North Jakarta from August to O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Multiple studies have indicated that anxiety with worry and extreme anxiety could be used as diagnostic indicators of insomnia [ 133 - 135 ]. A cross-sectional study confirms the relationship between anxiety and poor sleep quality among the Indonesian population [ 136 ]. Depression and insomnia are bidirectionally correlated, and both enhance the risk of each other [ 137 , 138 ].…”
Section: Common Complications Of Insomniamentioning
confidence: 82%
“…Multiple studies have indicated that anxiety with worry and extreme anxiety could be used as diagnostic indicators of insomnia [ 133 - 135 ]. A cross-sectional study confirms the relationship between anxiety and poor sleep quality among the Indonesian population [ 136 ]. Depression and insomnia are bidirectionally correlated, and both enhance the risk of each other [ 137 , 138 ].…”
Section: Common Complications Of Insomniamentioning
confidence: 82%